Term stillbirths in Eastern Uganda: a community-based prospective cohort study - Martin Chebet; Peter Olupot-Olupot; Andrew D Weeks; Ingunn Marie S Engebretsen; Noela Regina Akwi Okalany; Francis Okello; Thorkild Tylleskär; Kathy Burgoine; David Mukunya (Global Health Action)
Background Every year, 1.9 million stillbirths occur worldwide, of whom 1.5 million occur in sub-Saharan Africa (SSA) and Southeast Asia. Objectives This study aims to determine the incidence and risk factors and to describe underlying causes for term stillbirths in Eastern Uganda. Methods This was a cohort study of pregnant women enrolled at 34 weeks of gestation or more and followed to birth between January 2021 and January 2024. Enrolment and follow-up were done in the community by trained midwives. Using structured questionnaires, details of maternal health, pregnancy and birth were captured. Results We enrolled 6101 participants and analysed 5496 for incidence of term stillbirth and 5296 for risk factors. Of the participants, 4913/5296 (92.8%) were between 14 and 35 years, and 4456/5296 (84.1%) had a health facility birth. There were 101 term stillbirths (61 were intrapartum and 40 antepartum). The incidence of term stillbirth was 18.4 per 1000 births (95% CI 14.8 to 22.9). The most common underlying causes of stillbirth were prolonged or obstructed labour 32/101 (31.7%) and malaria 20/101 (19.8%). The factors associated with term stillbirths were caesarean birth (aRR 3.3; 95% CI 2.00 to 5.4), intimate partner violence (aRR 1.8; 95% CI 1.1 to 2.8) and maternal age above 35 years (aRR 2.2; 95% CI 1.2 to 3.9). Conclusion Eastern Uganda has a high rate of term stillbirths with more than half occurring during labour. Efforts are needed to improve the quality of birth care and to prevent intimate partner violence.